ANALISIS MATERI VIDEO LEARN GERMAN UNTUK PEMBELAJARAN KETERAMPILAN MENULIS DIALOG KELAS XI SEMESTER II - Pramesti, Chintya Nurika; Wahyuningsih, Fahmi (LATERNE, 2022)
Writing skill is considered as the most complicated and complex language skill. The internet has become a very important part of the education sector in the pandemic era. There are various kinds of teaching materials that can be accessed on the internet to make it easier for students to learn. A Youtube application that provides many channels to discuss German lessons, one of which is the Learn German channel. The video analyzed in this scientific article is entitled Learn German - das Restaurant which focuses on the Essen und trinken sub-theme. To confirm whether this channel is suitable as a learning material, therefore the formulation of the problem in this scientific article is how the YouTube Learn German channel video is suitable for learning German dialogue writing skills in class XI Semester II. The purpose of this scientific article is to describe the results of the analysis of the suitability of the video content of the Learn German Youtube channel for learning German dialogue writing skills for class XI semester II. This scientific article was written using a qualitative method whose data will be analyzed using Prastowo’s teaching material selection criteria from the results of the literature study. The source of data in writing this scientific article is the Youtube Learn German - das Restaurant video taken from the Learn German Youtube channel, the data for writing this article is the content of the material in the Youtube Learn German - das Restaurant video. Based on the video analysis, the percentage of eligibility for the suitability of the criteria for selecting learning materials is 87.5% using a Likert scale so that it is said to be very suitable to be used as learning material for the 2013 curriculum in learning German dialogue writing skills in SMA class XI with the theme Alltagsleben sub-theme Essen und trinken.